2022
DOI: 10.1007/s11033-022-07262-y
|View full text |Cite
|
Sign up to set email alerts
|

Pyrimethamine inhibits cell growth by inducing cell senescence and boosting CD8+ T-cell mediated cytotoxicity in colorectal cancer

Abstract: Background The emergence of nonresponse or resistance to traditional chemotherapeutic agents is one of the main challenges of colorectal cancer (CRC) therapies. Thus, novel therapeutic drugs that can improve the clinical outcomes of CRC patients are urgently needed. The purpose of this study was to investigate the effects and mechanisms of pyrimethamine in CRC. Methods and results In this study, we assessed the role of pyrimethamine on CRC cell growth by c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 39 publications
(44 reference statements)
0
5
0
Order By: Relevance
“…Recent findings by Marín et al [ 71 ] support our results, as they demonstrated that senescent melanoma cells stimulate the activation of tumor-reactive CD8 + tumor-infiltrating T cells, promoting anticancer immune surveillance. A correlation between induced cancer cell senescence and infiltration of CD8 + cells was also recently demonstrated in colorectal cancer after pyrimethamine treatment [ 72 ].…”
Section: Discussionmentioning
confidence: 80%
“…Recent findings by Marín et al [ 71 ] support our results, as they demonstrated that senescent melanoma cells stimulate the activation of tumor-reactive CD8 + tumor-infiltrating T cells, promoting anticancer immune surveillance. A correlation between induced cancer cell senescence and infiltration of CD8 + cells was also recently demonstrated in colorectal cancer after pyrimethamine treatment [ 72 ].…”
Section: Discussionmentioning
confidence: 80%
“…As shown in Figures 4A, B , the IC50 of the TMEscore-H group was not significantly different to that of the TMEscore-L group for cisplatin and docetaxel (P>0.05), but was significantly different for 5-fluorouracil, gemcitabine, and paclitaxel ( Figures 4C–E ). Furthermore, five chemotherapy drugs (temozolomide ( 24 ), pyrimethamine ( 25 ), lapatinib ( 26 ), doxorubicin ( 27 ), and ruxolitinib ( 28 )), which are reported to be associated with the treatment of CRC, showed significant differences between the TMEscore-H and TMEscore-L groups ( Figures 4F–J ). Thereafter, the expression levels of six known immune checkpoint inhibitors, namely PD1 (PDCD1), PD-L1, PD-L2 (PDCD1LG2), CD80, CD86, CTLA4, and CD274, were compared based on the TMEscore clusters.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, 12 immunotherapy drugs about PDAC from GDSC websites were filtered, which paves the way for patients with PDAC in medical treatments. Pyrimethamine (2,4-diamino-5-p-chlorophenyl-6-ethylpyrimidine), a dihydrofolate reductase (DHFR) inhibitor, is used for treating malaria by inhibiting the proliferation of plasmodium and toxoplasma and also applied to anti-tumor field [ 36 ]. Furthermore, Phenformin, a common biguanide drug, can effectively treat diabetes.…”
Section: Discussionmentioning
confidence: 99%